STATUS GIZI DAN KONTRIBUSI KONSUMSI MAKANAN JAJANAN ANAK SEKOLAH DI SD 2 PENATIH DENPASAR TIMUR - Ni Putu Ratih Mudiani; Hertog Nursanyoto; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Abstract. Nutritional status of school children snack food consumption contribution, children who are in SD 2 Penatih. . The purpose of this study was to determine the  overview of nutrition and snack food consumption in primary school children in 2 Penatih The sample used is a child who is in grade 4 and 5 are male students men and women who were in elementary school 2 Penatih.  Sought is the method of recall 2 x 24 hours, type of research is observational research with cross sectional design where, research done by making observations on the nutritional status of school children and the consumption of street food. From the research that has been done is obtained in the energy consumption of street food samples largely categorized either by 10 samples with good nutritional status of as many as 6 sample (60,0%)s  more than enough samples that category is less and less category of  1 samples  with good nutritional status of 1 samples (100%) and were categorized enough for 44 samples with good nutritional status 27 sample (61,0%) and protein consumption snacks on most of the samples are categorized either 10 samples  with good nutritional status of as many as 7 samples (70,0%) more than enough samples that category is less and less categories by 7 samples with good nutritional status of 34 samples (62,0%) and were categorized fairly by 38 samples with good nutritional status of as many as 21 samples (55,0%). Keywords: Nutritional Status, Snack Consumption, Microtoice, Weigher.